The first record of Agoo Bahder & Bartlett, 2019 (Hemiptera: Fulgoroidea: Derbidae) for the state of Amazonas, Brazil, with the description of a new species - Cantanhede , Inezita; Viegas, Eduarda F. G.; Ale-Rocha, Rosaly (Entomological Communications, 2024)
For the first time, the occurrence of the genus Agoo Bahder & Bartlett, 2019 (Hemiptera: Fulgoroidea: Derbidae) was recorded in the state of Amazonas, Brazil, through the discovery of a new species for the genus. Additionally, we describe and illustrate Agoo galbina sp. nov. and present a geographic distribution map of Brazilian species based on literature data.